Basal-Plane Functionalization of Chemically Exfoliated Molybdenum Disulfide by Diazonium Salts - Knirsch, Kathrin; Nerl, Hannah C.; Cucinotta, Clotilde S.; Berner, Nina; Gholamvand, Zahra; McEvoy, Niall; Wang, Zhenxing; Abramovic, Irena; Vecera, Philipp; Halik, Marcus; Sanvito, Stefano; Duesberg, Georg S.; et al. (ACS nano, 2015)
Although transition metal dichalcogenides such as MoS2 have been recognized as highly potent two-dimensional nanomaterials, general methods to chemically functionalize them are scarce. Herein, we demonstrate a functionalization route that results in organic groups bonded to the MoS2 surface via covalent C-S bonds. This is based on lithium intercalation, chemical exfoliation and subsequent quenching of the negative charges residing on the MoS2 by electrophiles such as diazonium salts. Typical degrees of functionalization are 10-20 atom % and are potentially tunable by the choice of intercalation conditions. Significantly, no further defects are introduced, and annealing at 350 °C restores the pristine 2H-MoS2. We show that, unlike both chemically exfoliated and pristine MoS2, the functionalized MoS2 is very well dispersible in anisole, confirming a significant modification of the surface properties by functionalization. DFT calculations show that the grafting of the functional group to the sulfur atoms of (charged) MoS2 is energetically favorable and that S-C bonds are formed.
Keywords: 1T-polytype; basal-plane; chemical exfoliation; covalent functionalization; layered materials; molybdenum disulfide; transition metal dichalcogenides

Covalent Bisfunctionalization of Two-Dimensional Molybdenum Disulfide - Chen, Xin; Bartlam, Cian; Lloret Segura, Vicente Josep; Moses Badlyan, Narine; Wolff, Stefan; Gillen, Roland; Stimpel-Lindner, Tanja; Maultzsch, Janina; Duesberg, Georg S.; Knirsch, Kathrin; Hirsch, Andreas (Angewandte Chemie International Edition, 2021)
Covalent functionalization of two-dimensional molybdenum disulfide (2D MoS2) holds great promise in developing robust organic-MoS2 hybrid structures. Herein, for the first time, we demonstrate an approach to building up a bisfunctionalized MoS2 hybrid structure through successively reacting activated MoS2 with alkyl iodide and aryl diazonium salts. This approach can be utilized to modify both colloidal and substrate supported MoS2 nanosheets. We have discovered that compared to the adducts formed through the reactions of MoS2 with diazonium salts, those formed through the reactions of MoS2 with alkyl iodides display higher reactivity towards further reactions with electrophiles. We are convinced that our systematic study on the formation and reactivity of covalently functionalized MoS2 hybrids will provide some practical guidance on multi-angle tailoring of the properties of 2D MoS2 for various potential applications.
CRIS-Team WoS Importer:2021-05-14

Covalent Patterning of 2D MoS2 - Chen, Xin; Kohring, Malte; Assebban, M'hamed; Tywoniuk, Bartlomiej; Bartlam, Cian; Moses Badlyan, Narine; Maultzsch, Janina; Duesberg, Georg S.; Weber, Heiko B.; Knirsch, Kathrin; Hirsch, Andreas (Chemistry - A European Journal, 2021)
The development of an efficient method to patterning 2D MoS2 into a desired topographic structure is of particular importance to bridge the way towards the ultimate device. Herein, we demonstrate a patterning strategy by combining the electron beam lithography with the surface covalent functionalization. This strategy allows us to generate delicate MoS2 ribbon patterns with a minimum feature size of 2 μm in a high throughput rate. The patterned monolayer MoS2 domain consists of a spatially well-defined heterophase homojunction and alternately distributed surface characteristics, which holds great interest for further exploration of MoS2 based devices.
CRIS-Team Scopus Importer:2021-08-13
Keywords: functionalization; MoS; patterning; PL; Raman spectroscopy

Defect Engineering of Two-Dimensional Molybdenum Disulfide - Chen, Xin; Denninger, Peter; Stimpel-Lindner, Tanja; Spiecker, Erdmann; Duesberg, Georg S.; Backes, Claudia; Knirsch, Kathrin; Hirsch, Andreas (Chemistry - A European Journal, 2020)
Two-dimensional (2D) molybdenum disulfide (MoS2) holds great promise in electronic and optoelectronic applications owing to its unique structure and intriguing properties. The intrinsic defects such as sulfur vacancies (SVs) of MoS2 nanosheets are found to be detrimental to the device efficiency. To mitigate this problem, functionalization of 2D MoS2 using thiols has emerged as one of the key strategies for engineering defects. Herein, we demonstrate an approach to controllably engineer the SVs of chemically exfoliated MoS2 nanosheets using a series of substituted thiophenols in solution. The degree of functionalization can be tuned by varying the electron-withdrawing strength of substituents in thiophenols. We find that the intensity of 2LA(M) peak normalized to A1g peak strongly correlates to the degree of functionalization. Our results provide a spectroscopic indicator to monitor and quantify the defect engineering process. This method of MoS2 defect functionalization in solution also benefits the further exploration of defect-free MoS2 for a wide range of applications.
CRIS-Team Scopus Importer:2020-05-02
Keywords: 2D materials; defect engineering; functionalization; MoS; thiophenol

Functionalisation of Graphene Sensor Surfaces for the Specific Detection of Biomarkers - Von Lueders, Laura; Tilmann, Rita; Lee, Kangho; Bartlam, Cian; Stimpel-Lindner, Tanja; Nevanen, Tarja K.; Iljin, Kristiina; Knirsch, Kathrin; Hirsch, Andreas; Duesberg, Georg S. (Angewandte Chemie International Edition, 2023)
We report on a controllable and specific functionalisation route for graphene field-effect transistors (GFETs) for the recognition of small physiologically active molecules. Key element is the noncovalent functionalisation of the graphene surface with perylene bisimide (PBI) molecules directly on the growth substrate. This Functional Layer Transfer enables the homogeneous self-assembly of PBI molecules on graphene, onto which antibodies are subsequently immobilised. The sensor surface was characterised by atomic force microscopy, Raman spectroscopy and electrical measurements, showing superior performance over conventional functionalisation after transfer. Specific sensing of small molecules was realised by monitoring the electrical property changes of functionalised GFET devices upon the application of methamphetamine and cortisol. The concentration dependent electrical response of our sensors was determined down to a concentration of 300 ng ml−1 for methamphetamine.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Antibody-Antigen System; Biosensors; Functional Layer Transfer; Graphene; Noncovalent Functionalization

Functionalization of graphene by electrophilic alkylation of reduced graphite - Englert, Jan; Knirsch, Kathrin; Dotzer, Christoph; Butz, Benjamin; Hauke, Frank; Hirsch, Andreas; Spiecker, Erdmann (Chemical Communications, 2012)
The reaction of Na/K-reduced graphite with hexyliodide represents a new, versatile and mild approach to synthesize alkylated graphene derivatives, which were characterized by a combination of Raman spectroscopy, TEM and TGA/MS analysis. © The Royal Society of Chemistry 2012.

Highly Selective Non-Covalent On-Chip Functionalization of Layered Materials - Tilmann, Rita; Weiß, Corinna; Cullen, Conor P.; Peters, Lisanne; Hartwig, Oliver; Hoeltgen, Laura; Stimpel-Lindner, Tanja; Knirsch, Kathrin; Mcevoy, Niall; Hirsch, Andreas; Duesberg, Georg S. (Advanced Electronic Materials, 2021)
Non-covalent functionalization of layered 2D materials is an essential tool to modify and fully harness their optical, electrical, and chemical properties. Herein, a facile method enabling the selective formation of self-assembled monolayers (SAMs) of perylene bisimide (PBI) on transition metal dichalcogenides (TMDs), directly on the growth substrate (on-chip), is presented. Laterally-resolved infrared atomic force microscopy (AFM-IR) and time-of-flight secondary ion mass spectrometry (TOF-SIMS) are applied as superior techniques to gain detailed information beyond traditional surface analysis techniques, such as Raman spectroscopy and AFM, on TMD/PBI structures. The highly selective functionalization conducted in organic solution on MoS2 and WSe2 opens up a pathway to controllable, versatile functionalization of layered materials, which is highly sought after for its potential in passivation, tuning of properties and applications in optics, electronics, and (bio-) sensing.
CRIS-Team Scopus Importer:2021-01-29
Keywords: 2D materials; perylene bisimides; self-assembled monolayers; surface functionalization; transition metal dichalcogenides

Laser-Triggered Bottom-Up Transcription of Chemical Information: Toward Patterned Graphene/MoS2 Heterostructures - Chen, Xin; Assebban, M'hamed; Kohring, Malte; Bao, Lipiao; Weber, Heiko B.; Knirsch, Kathrin; Hirsch, Andreas (Journal of the American Chemical Society, 2022)

Mono- and Ditopic Bisfunctionalization of Graphene - Knirsch, Kathrin; Schäfer, Ricarda; Hauke, Frank; Hirsch, Andreas (Angewandte Chemie International Edition, 2016)
For the first time, the bisfunctionalization of graphene by employing two successive reduction and covalent bond forming steps is reported. Bulk functionalization in dispersion and functionalization of individual sheets deposited on surfaces have both been carried out. Whereas in the former case attacks from both sides of the basal plane are possible and can lead to strain-free architectures, in the latter case, retrofunctionalizations can become important when the corresponding anion of the addend is a sufficiently good leaving group.
Keywords: functionalization; graphene; Raman spectroscopy; retrofunctionalization; topicity

Noncovalent Liquid Phase Functionalization of 2H-WS2with PDI: An Energy Conversion Platform with Long-Lived Charge Separation - Scharl, Tobias; Binder, Gerhard; Chen, Xin; Yokosawa, Tadahiro; Cadranel, Alejandro; Knirsch, Kathrin; Spiecker, Erdmann; Hirsch, Andreas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2022)
Transition metal dichalcogenides are attractive 2D materials in the context of solar energy conversion. Previous investigations have focused predominantly on the properties of these systems. The realization of noncovalent hybrids with, for example, complementary electroactive materials remains underexplored to this date for exfoliated WS2. In this contribution, we explore WS2 by means of exfoliation and integration together with visible light-absorbing and electron-accepting perylene diimides into versatile electron-donor acceptor hybrids. Important is the distinct electron-donating feature of WS2. Detailed spectroscopic investigations of WS2-PDI confirm the electron donor/acceptor nature of the hybrid and indicate that green light photoexcitation leads to the formation of long-lived WS2+-PDIcharge-separated states.
CRIS-Team Scopus Importer:2022-04-14

Oxidation and phase transition in covalently functionalized MoS2 - Moses Badlyan, Narine; Pettinger, Nina; Enderlein, Niklas; Gillen, Roland; Chen, Xin; Zhang, Wanzheng; Knirsch, Kathrin; Hirsch, Andreas; Maultzsch, Janina (Physical Review B, 2022)
We present a Raman study of MoS2 powders and MoS2 individual layers covalently functionalized with organic molecules. In MoS2 powders, the defect-induced "LA"Raman mode shows evidence for successful functionalization. Increasing temperature induces oxidation of both functionalized and nonfunctionalized MoS2 into MoO3. In contrast, mechanically exfoliated individual MoS2 layers do not transfer into MoO3 under the same conditions. Instead, the Raman spectra show that the procedure of covalent functionalization leads to a partial transition from the 2H into the 1T' crystallographic phase in few-layer MoS2. We support the identification of the 1T' phase by DFT calculations of the corresponding vibrational modes in the mono- and bilayer 1T'-MoS2.
CRIS-Team Scopus Importer:2022-09-30

Patterned Assembly of Transition Metal Dichalcogenide/Graphene Heterostructures via Direct Laser Writing - Chen, Xin; Wolff, Stefan; Zuieva, Sofiia; Schusterbauer, Robert; Shaikh, Rida Mansoor; Halbig, Christian E.; Habel, Anton; Gillen, Roland; Knirsch, Kathrin; Donskyi, Ievgen; Eigler, Siegfried; Maultzsch, Janina; et al. (Advanced Functional Materials, 2025)
Connecting two-dimensional (2D) material layers via interface linkers represents a new avenue for fabricating 2D heterostructures. Utilizing light to remotely modulate this interface function allows for seamless assembly and patterning in a single run. Here, an efficient method for fabricating patterned 2D heterostructures using direct laser writing is demonstrated, drawing a conceptual parallel to laser printing. In the approach, functionalized transition metal dichalcogenide (TMD) dispersions serve as inks, graphene as the substrate, and a Raman laser as the patterning tool. Unlike laser printing's electrostatic interactions, the method achieves patterned assembly through covalent bonding between TMDs and graphene. Selective Raman laser irradiation of functionalized TMD/graphene heterostructures triggers localized reactions, forming chemically modified domains exclusively in the laser-irradiated regions, as confirmed by Raman spectroscopy, Kelvin probe force microscopy (KPFM), and time-of-flight secondary ion mass spectrometry (ToF-SIMS). Experimental and theoretical analyses of the interface composition and structure provide new insights into laser-induced chemistry. The work demonstrates the potential for high-throughput assembly of customizable 2D heterostructures, with enhanced compatibility for subsequent patterning through photolabile linkers and photoinduced coupling. Additionally, the results provide deeper insights into chemistry within confined 2D spaces, offering a novel approach to nanoscale heterostructure engineering.
CRIS-Team Scopus Importer:2025-05-30
Keywords: 2D heterostructures; interface engineering; laser writing; patterning; transition metal dichalcogenides

Scanning-Raman-microscopy for the statistical analysis of covalently functionalized graphene - Englert, Jan; Vecera, Philipp; Knirsch, Kathrin; Schäfer, Ricarda; Hauke, Frank; Hirsch, Andreas; Hauke, Frank (Acs Nano, 2013)
We report on the introduction of a systematic method for the quantitative and reliable characterization of covalently functionalized graphene based on Scanning-Raman-Microscopy (SRM). This allows for recording and analyzing several thousands of Raman spectra per sample and straightforward display of various Raman properties and their correlations with each other in histograms or coded 2D-plots. In this way, information about the functionalization efficiency of a given reaction, the reproducibility of the statistical analysis, and the sample homogeneity can be easily deduced. Based on geometric considerations, we were also able to provide, for the first time, a correlation between the mean defect distance of densely packed point defects and the Raman I/I ratio directly obtained from the statistical analysis. This proved to be the prerequisite for determining the degree of functionalization, termed θ. As model compounds, we have studied a series of arylated graphenes (GPh) for which we have developed new synthetic procedures. Both graphite and graphene grown by chemical vapor deposition (CVD) were used as starting materials. The best route toward GPh consisted of the initial reduction of graphite with a Na/K alloy in 1,2-dimethoxyethane (DME) as it yields the highest overall homogeneity of products reflected in the widths of the Raman I /I histograms. The Raman results correlate nicely with parallel thermogravimetric analysis (TGA) coupled with mass spectrometry (MS) studies. © 2013 American Chemical Society.

Screening of the chemical reactivity of three different graphite sources using the formation of reductively alkylated graphene as a model reaction - Knirsch, Kathrin; Englert, Jan; Dotzer, Christoph; Hauke, Frank; Hirsch, Andreas; Hauke, Frank (Chemical Communications, 2013)
Reductive alkylation of three graphite starting materials G(flake), G(powder), and G(spherical) reveals pronounced differences in the obtained covalently functionalized graphene with respect to the degree of functionalization, exfoliation efficiency and product homogeneity, as demonstrated by statistical Raman microscopy (SRM), TGA/MS, IR-spectroscopy and solubility behavior.This journal is © The Royal Society of Chemistry 2013.

Topology-Driven Reductive Silylation of Synthetic Carbon Allotropes - Knirsch, Kathrin; Hof, Ferdinand; Lloret Segura, Vicente Josep; Mundloch, Udo; Hauke, Frank; Hirsch, Andreas (Journal of the American Chemical Society, 2016)